Kidney cancer biobanking: considerations for a single institutional biorepository - Del Vecchio, Sharon J. (Transl Androl Urol, 2019)
The Princess Alexandra Hospital Kidney Cancer Biobank, housed at the Translational Research Institute in Brisbane, is an Australian biorepository which contains fixed and fresh-frozen cancer and non-cancer kidney tissue, perinephric fat, urine and peripheral blood. The patient samples are linked to de-identified clinical information via a secure database. Participants undergoing nephrectomy for suspected renal malignancy are recruited prospectively. Recruitment began in 2013 and the biobank currently contains biofluids, tissue and clinical information for more than 330 participants. This biobank contains linked de-identified clinical data, which provide comprehensive information about biospecimens, and information about clinical outcomes.